2016
DOI: 10.1002/cvj.12037
|View full text |Cite
|
Sign up to set email alerts
|

Faith as a Cultural Variable: Implications for Counselor Training

Abstract: Counselors are faced with a unique challenge when faith is a prominent clinical variable. Although faith is deemed relevant, counselors may not feel comfortable approaching the subject of faith with clients. Participants in this study were practicing counselors licensed in their respective states; each was also a current doctoral candidate in counselor education and supervision. A scenario involving a complex interaction of faith; family systems; and lesbian, gay, bisexual, and transgender issues in clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…More recently, however, counselors are recognizing the importance of the divinity domain (Kelly, ). For example, Scott, Sheperis, Simmons, Rush‐Wilson, and Milo () conducted a qualitative study with faith (divinity domain) as an important cultural variable in their study's primary case study. Scott et al concluded that counselors are uncertain about how to integrate the divinity domain (i.e., faith) as a treatment priority even when they recognize its importance to clients' self‐understanding.…”
Section: Moral Foundations Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, however, counselors are recognizing the importance of the divinity domain (Kelly, ). For example, Scott, Sheperis, Simmons, Rush‐Wilson, and Milo () conducted a qualitative study with faith (divinity domain) as an important cultural variable in their study's primary case study. Scott et al concluded that counselors are uncertain about how to integrate the divinity domain (i.e., faith) as a treatment priority even when they recognize its importance to clients' self‐understanding.…”
Section: Moral Foundations Theorymentioning
confidence: 99%
“…Some counselors may experience a sense of cultural difference from their clients when clients not only demote autonomy to third place but also see community and divinity as dynamically intertwined. Many counselors may be clinically stretched to intervene with spiritually devoted clients (i.e., clients who prioritize a purity/sanctity moral foundation) in a manner that is culturally sensitive and ethically responsible (Frame, ; Pargament, ; Plante, ; Scott et al, ). Pargament () emphasized the importance of openness to learning when addressing spirituality in therapy, noting there is “no room for the intolerance that can be found in rejectionism or untempered exclusivism in spiritually integrated psychotherapy” (p. 191).…”
Section: Moral Foundations Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The MSJCC, departing from the relatively heavy focus on race/ethnicity embedded within the MCC, emphasize privileged/marginalized social statuses and identities of the counselor and client and provide an opportunity to reenvision multiculturally competent practice in relation to an often‐neglected area of diversity: religion and/or spirituality (R/S). This need is reinforced by Scott, Sheperis, Simmons, Rush‐Wilson, and Milo (), who noted that “faith or religion is often not a target of multicultural training; therefore, professional counselors may be less skilled in working within this construct” (p. 201). Given that R/S may not be addressed as a multicultural issue in training, it is essential that counselors understand the R/S of their clients and serve as social justice advocates for all multicultural issues, including R/S.…”
mentioning
confidence: 99%